2017
DOI: 10.1038/s41598-017-07530-z
|View full text |Cite
|
Sign up to set email alerts
|

Angulin proteins ILDR1 and ILDR2 regulate alternative pre-mRNA splicing through binding to splicing factors TRA2A, TRA2B, or SRSF1

Abstract: Angulin proteins are a group of evolutionally conserved type I transmembrane proteins that contain an extracellular Ig-like domain. In mammals, three angulin proteins have been identified, namely immunoglobulin-like domain containing receptor 1 (ILDR1), immunoglobulin-like domain containing receptor 2 (ILDR2), and lipolysis-stimulated lipoprotein receptor (LSR). All three proteins have been shown to localize at tight junctions (TJs) and are important for TJ formation. Mutations in ILDR1 gene have been shown to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 51 publications
2
23
0
Order By: Relevance
“…Mutations of ILDR1 gene are associated with autosomal recessive hearing impairment DFNB42, and knockout of Ildr1 gene in mice leads to degeneration of mechanosensory cochlear hair cells, resulting in hearing loss [22]. Our previous data showed that ILDR1 interacts with a series of splicing factors and regulates alternative splicing [23]. In the present work, we demonstrate that ILDR1 promotes IAV replication through interacting with PLSCR1.…”
Section: Introductionsupporting
confidence: 63%
“…Mutations of ILDR1 gene are associated with autosomal recessive hearing impairment DFNB42, and knockout of Ildr1 gene in mice leads to degeneration of mechanosensory cochlear hair cells, resulting in hearing loss [22]. Our previous data showed that ILDR1 interacts with a series of splicing factors and regulates alternative splicing [23]. In the present work, we demonstrate that ILDR1 promotes IAV replication through interacting with PLSCR1.…”
Section: Introductionsupporting
confidence: 63%
“…Splicing factors SRRM4, SFSWAP, and ESRP1 play important roles in the inner ear, albeit none of them has been shown to regulate the alternative splicing of Cdh23 exon 68 [ 18 20 ]. We previously showed that deafness-related protein ILDR1 and its homolog ILDR2 regulate alternative splicing through binding to splicing factors TRA2A, TRA2B, and SRSF1 [ 21 ]. We also found that RNA-binding protein RBM24 is specifically expressed in the hair cells [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…The yeast two-hybrid screen was performed as previously described [ 26 28 ]. Briefly, yeast strain AH109 (Clontech) was sequentially transformed with the bait plasmid and a chicken cochlear cDNA library in the HybriZAP two-hybrid vector [ 29 ].…”
Section: Methodsmentioning
confidence: 99%